(untitled) (Research, Society and Development, 2022)
Introduction: The COVID-19 pandemic affects the entire system, one of the areas that was health was prenatal care. Object: The present study sought to evaluate the influence of COVID-19 on the difficulty of gestational syphilis and its relationship with the Human Development Index (HDI) of Primary Care in the state of Santa Catarina. Method: we analyzed the cases of gestational syphilis that were reported in the micro-regions, in the macro-regions of health of Santa Catarina, in addition to some pole municipalities. Data available in the Notifiable Diseases Information System (SINAN) provided by the Santa Catarina Epidemiological Surveillance Board (DIVE) were analyzed. The following variables were used: year of diagnosis, macro-region, micro-region and city. A data collection was also carried out regarding the HDI of primary care in the cities used for the study in the System of Indicators of Sustainable Municipal Development. Results: The Greater Florianópolis macro-region showed the largest reduction in 2020, 34.4% compared to the previous year. Among the microregions, Xanxerê showed the greatest reduction (-42.5%). The one in Vale Itapoacu, on the other hand, had an increase of 80%. The hub city of Florianópolis had the biggest reduction (77%), Jaraguá do Sul showed the biggest increase 187%. Conclusion: there was a decrease in the number of diagnoses during the pandemic. In relation to the Primary Care HDI, in some municipalities, this relationship was evident, in others, not so much. Also, the hypothesis was raised that the culture of some regions had an impact on the prenatal segment.